Estivation and Postestivation Development of Hemlock Woolly Adelgid (Adelges tsugae) (Hemiptera: Adelgidae) at Different Temperatures. Issue 6 (4th November 2022) - Limbu, Samita; Keena, Melody A; Dietschler, Nicholas; O'Connor, Katharine; Whitmore, Mark C
Abstract: Hemlock woolly adelgid ( Adelges tsugae ) is the most important pest of hemlocks in the eastern United States, where it completes three generations a year. We investigated the impact of temperature (8, 12, 16, and 20°C) on the estivation and postaestivation stages of the A. tsugae sistens generation. Temperature significantly impacted development and survival of this generation. The highest mortality occurred at the coolest temperature (8°C). Adelges tsugae developed rapidly as the temperature increased and optimum temperatures for development ranged between 17 and 22°C for the different instars. The estimated lower temperature threshold was 0°C for second instar nymphs and 3 –5°C for the other instars and the preoviposition period. Estivating first-instar sistentes resumed development (as evidenced by segments becoming visible) after 40–100 d at the constant temperatures (fastest at 16°C) then required only 105 degree-days (DD) for 50% of the individuals to molt. Subsequent instars developed rapidly (another 470 DD total to reach adult), and oviposition began at 623 DD from the time the first instars resumed development. This study provides valuable data required to develop an annual phenology model for A. tsugae which will assist in timing monitoring and control treatments. Graphical Abstract: